2010
DOI: 10.1103/physrevc.82.034602
|View full text |Cite
|
Sign up to set email alerts
|

α-particle production inHe6+Sn

Abstract: The collision 6 He + 120 Sn has been investigated at four energies near the Coulomb barrier. A large yield of α particles has been detected, with energies around the energy of the scattered 6 He beam. The energy and angular distributions of the α particles have been analyzed and compared with breakup and neutron transfer calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
71
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(85 citation statements)
references
References 32 publications
9
71
2
3
Order By: Relevance
“…6 He reactions near the Coulomb barrier Alpha-particles from the breakup of 6 He on a 120 Sn target were observed by deFaria et al [23]. The α-particle energies and angular distributions led to conclusions about the reaction mechanism that agreed with those discussed in ref.…”
Section: α-Particle Production Insupporting
confidence: 76%
“…6 He reactions near the Coulomb barrier Alpha-particles from the breakup of 6 He on a 120 Sn target were observed by deFaria et al [23]. The α-particle energies and angular distributions led to conclusions about the reaction mechanism that agreed with those discussed in ref.…”
Section: α-Particle Production Insupporting
confidence: 76%
“…It is also observed that the breakup channel slightly damps the so called Coulomb rainbow peak and increases the cross section at angles larger than the rainbow peak. The same qualitative effect has been recently observed in 6 He+ 58 Ni [15], 11 Li + 208 Pb [17] and 11 Be + 64 Zn [18] scattering. It also has been shown [32] that the damping of the Coulomb rainbow peak for the 8 B + 208 Pb, 58 Ni systems involving proton-halo projectiles is smaller than for the systems involving neutron-halo projectiles (like 11 Li and 6 He) because the dipole response of the 8 B is less.…”
Section: B Cdcc Analysissupporting
confidence: 60%
“…Such nuclei are unstable by beta emission or electron capture, with relatively long lifetimes (milliseconds up to seconds), sufficient to produce a secondary beam. Light exotic nuclei usually present a pronounced cluster structure, with very low separation energies in comparison to their stable partners and can be found either in the neutron rich [9][10][11][12][13][14][15][16][17][18] or in the proton rich sides [19][20][21][22][23][24] of the nuclear chart. One of these nuclei is 8 B which is formed by a 7 Be core plus one proton bound by only 0.137 MeV to the core.…”
Section: Introductionmentioning
confidence: 99%
“…The 6 He is a radioactive nucleus that has a small breakup threshold energy of S n = 0.973 MeV (into 4 He+2n) and is particularly interesting since its core could explain the alpha particle production observed in the scattering of 6 He on heavy targets such as 120 Sn [9]. Moreover an energy dependence on the surface imaginary optical potential part has been observed, which indicates that, as the energy decreases, the reactions become more peripheral for the 6 He+ 120 Sn [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent works have been demonstrated that there is an enhancement of the total reaction cross sections for weakly bound and unstable systems such as 7,9 7 Be+ 58 Ni, 6 He+ 64 Zn, 6 He+ 120 Sn, 7 Be, 6 Li+ 12 C when compared with tightly stable projectiles such as 4 He or 16 O [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%